Optimizing the Fulfillment of Prisoners' Health Rights: A Case Study at Class IIA Correctional Facility - Maskawati; Burhanuddin, (International Journal of Scientific Research and Management (IJSRM), 2024)
This study explores the fulfillment of health rights for inmates at the Class IIA Watampone Correctional Facility, focusing on the provision of adequate healthcare services and the challenges faced in ensuring prisoners' health rights. Despite the legal frameworks guaranteeing the right to health for all citizens, including inmates, significant discrepancies remain in the quality of healthcare provided in correctional facilities. Using an empirical approach, this research examines the existing healthcare systems, resources, and challenges in the prison environment, relying on observations and interviews with correctional officers and healthcare personnel. The study highlights the impact of overcrowding, insufficient healthcare staff, and lack of specialized services as key barriers to effective healthcare delivery. It also emphasizes the need for increased investment in medical infrastructure, staff training, and collaboration with national health systems to address these challenges. The findings underscore the importance of meeting the healthcare needs of inmates to fulfill legal obligations, improve rehabilitation outcomes, and promote public health. The study concludes with recommendations for improving healthcare conditions in prisons to ensure that inmates receive the care they are entitled to, which is crucial for their reintegration into society and the reduction of recidivism.